Transitional Cell Carcinoma of Lacrimal Sac Presenting as a Massive Swelling and Dacryohemorrhea - Purkayastha, Abhishek; Sharma, Neelam; Tyagi, Arvind Kumar; Vartak, Anushree; Solanki, Pramod (Indian Journal of Medical and Paediatric Oncology, 2019)
Transitional cell carcinomas (TCCs) of lacrimal sac are extremely uncommon neoplasms with high degree of invasiveness, local recurrence, and distant metastasis despite an aggressive treatment. They generally present with epiphora and lacrimal mass lesion but rarely dacryohemorrhea or bloody tears. We hereby report a 50-year-old female who presented with complaints of epiphora, blood in tears, and a progressive swelling measuring 8 cm × 5 cm over left lacrimal sac site. Biopsy from the swelling revealed TCC of lacrimal sac. Radiographic imaging showed a localized mass lesion lacrimal sac eroding adjacent structures, left orbital extension, and left cervical lymphadenopathy without any intracranial extension or distant metastasis. She underwent wide local excision of the primary lesion with left orbital exenteration, left partial maxillectomy, left anterior ethmoidectomy, and left forehead flap reconstruction followed by adjuvant conformal radiotherapy to local site to a dose of 60 Gy and ipsilateral neck to 50 Gy. Combined modality therapy showed satisfactory cosmesis and overall improved functionality on her first review at 6 weeks, however she lost to further follow-up. A thorough review of literature reveals that our case may be one of the largest TCC of lacrimal sac ever reported and the third case to present with dacryohemorrhea in world literature till date.
Keywords: Dacryohemorrhea; exenteration; lacrimal sac; radiotherapy; transitional cell carcinoma